2021
DOI: 10.3390/agriculture11040332
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Oat-Vetch Mixtures in Organic and Conventional Farming Systems

Abstract: The research aimed to compare the yields and yield components of mixtures of oats with common vetch grown for seeds in organic and conventional farming systems. Moreover, the selection of oat cultivars for the mixture and its performance in a crop rotation experiment in different growing years was analyzed. Additionally, the leaf area index (LAI) and the relative content of chlorophyll (SPAD) of the mixtures were assessed. The field experiment with four-field crop rotation in organic or conventional farming sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Various species provide complimentary use of environmental resources in a mixture in contrast to pure stands. The recent findings confirmed the benefits of intercropping, such as increased nitrogen uptake by cereals cultivated in a mixture with legumes [1][2][3], and more efficient use of water and nutrients in soil profile [4]. Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7].…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Various species provide complimentary use of environmental resources in a mixture in contrast to pure stands. The recent findings confirmed the benefits of intercropping, such as increased nitrogen uptake by cereals cultivated in a mixture with legumes [1][2][3], and more efficient use of water and nutrients in soil profile [4]. Different species in the mixtures also use field space more effectively [5], i.e., in weather conditions unfavorable for the growth of one species, the companion crop usually grows better [6,7].…”
supporting
confidence: 59%
“…In the case of well-established mixtures, e.g., oats-common vetch, where cereal component is more competitive toward the legume one, a proper selection of oat cultivars may also significantly affect the quantity and quality of the mixture's yield, i.e., protein content [1]. The oats-common vetch mixtures develop higher LAI and give a higher seed yield in the conventional farming system; however, the share of vetch seeds in the mixtures is higher in the organic system than in the conventional one [2].…”
mentioning
confidence: 99%
“…These results are similar to Sibi et al (2015) and Heydarzadeh et al (2022), who demonstrated the positive effect of these inoculum on the ash content for corn intercropping with green beans. It has been also published that inoculation with mycorrhizae increased ash content, given its beneficial role in promoting nutrient uptake, by adjusting pH or enzyme release (Puzynska et al, 2021). Furthermore, various inoculations resulted in a considerable increase in DM yield.…”
Section: Forage Quality and Yieldmentioning
confidence: 98%